SrCo1−xTixO3−δ perovskites as excellent catalysts for fast degradation of water contaminants in neutral and alkaline solutions - Miao, J.; Sunarso, J.; Su, C.; Zhou, W.; Wang, S.; Shao, Zongping (Nature Publishing Group, 2017)
Perovskite-like oxides SrCo1−xTixO3−δ (SCTx, x = 0.1, 0.2, 0.4, 0.6) were used as heterogeneous catalysts to activate peroxymonosulfate (PMS) for phenol degradation under a wide pH range, exhibiting more rapid phenol oxidation than Co3O4 and TiO2. The SCT0.4/PMS system produced a high activity at increased initial pH, achieving optimized performance at pH  ≥ 7 in terms of total organic carbon removal, the minimum Co leaching and good catalytic stability. Kinetic studies showed that the phenol oxidation kinetics on SCT0.4/PMS system followed the pseudo-zero order kinetics and the rate on SCT0.4/PMS system decreased with increasing initial phenol concentration, decreased PMS amount, catalyst loading and solution temperature. Quenching tests using ethanol and tert-butyl alcohol demonstrated sulfate and hydroxyl radicals for phenol oxidation. This investigation suggested promising heterogeneous catalysts for organic oxidation with PMS, showing a breakthrough in the barriers of metal leaching, acidic pH, and low efficiency of heterogeneous catalysis.